THE EFFECT OF GIVING GARLIC PEEL EXTRACT(Allium sativum) THROUGH DRINKING WATER TO THE PERCENTAGE OF INTERNAL ORGANS BROILER CHICKENS AGED 4 WEEKS - I K. W., Sanjaya; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of giving garlic peel extract ( Allium sativum ) through drinking water to the percentage of internal organs broiler chickens aged 4 weeks. The design used was a completely randomized design with 4 treatments and 4 replications each using 5 chickens so that the total number of chickens used was 80 chickens.The treatment in this study was given through drinking water with each treatment, namely P0 (Control) drinking water without garlic peel extract, P1 (drinking water containing 1% garlic peel extract), P2 (drinking water containing 2% garlic peel extract), P3 (drinking water containing 3% garlic peel extract). The variables observed were the percentage of liver, the percentage of the heart, the percentage of gall bladder, the percentage of the pancreas and the percentage of spleen.The results showed that the treatment of giving 1%, 2% and 3% garlic peel extract had no significant effect (P>0.05) on the percentage of internal organs broiler chickens aged 4 weeks. From this research, it can be said that giving 1%, 2% and 3% garlic peel extract through drinking water did not affect the percentage of internal organs broiler chickens aged 4 weeks. Keywords: broiler chicken, garlic peel extract, internal organs